Penerapan SOA (Service Oriented Architecture) dalam Pembuatan Sistem Informasi Izin Cuti Dosen dan Staff di Perguruan Tinggi - Hendri (Jurnal PROCESSOR, 2023)
The problem that often arises at Dinamika Bangsa University is that when a lecturer at the Kota Baru campus wants to apply for leave, they must get the signature of the Rector and Vice Rector 2 who are on the Thehok campus. The Rector and vice rector 2 have their own busy schedule, starting from academic meetings, teaching activities, seminar activities which often do not have time to meet in person with lecturers and staff who wish to apply for leave. The Service Oriented Architecture (SOA) method is a framework based on a system architecture that can integrate data stored strictly only in different locations or different sources. Lecturer and staff leave information systems in tertiary institutions can make it easier for higher education management to make decisions related to accepting or rejecting leave permits for lecturers and staff in tertiary institutions and also make it easier for lecturers who wish to apply for leave permits.